EDGE MACHINABILITY OF MDF EFFECT ON SURFACE QUALITY AND CONSEQUENCE FOR GLUING (Sciences & Technologie. B, Sciences de l'ingénieur, 2003)
MDF is becoming the basic wood-based material used in the furniture industry. The main goal of the research is the improvement of the machining process to produce edge surfaces with the required quality for a high gluing toughnessThe fracture energy ratio (G1c) is measured using cantilever beams samples and the results are analyzed to qualify the toughness of two planed MDF panel edges glued together.The chip thickness effect on G1c is clearly demonstrated by the experiments. Here, it is possible to find a linear relationship between G1c and surface roughness criterion (Ra). The allowed chip thickness is limited by the industrial milling conditionsWe can conclude that the chip thickness in the range 0.20 up to 0.35 is the most significant parameter for a high performance gluing